The Role of Landscape Work in Developing Creativity and Observational Skills in Students - Aslonov Furqat Botirovich (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: This article examines the significance of working in the landscape genre for the development of students’ creativity and observational skills in fine arts education. It discusses how landscape painting encourages careful observation of nature, critical analysis of visual elements, and the expression of personal artistic ideas. The study highlights the use of innovative teaching methods, such as interactive projects, digital visualization tools, outdoor painting (plein-air), and the “flipped classroom” approach, which enhance students’ engagement, foster independent thinking, and strengthen both artistic and cognitive abilities.